Sleep disturbance exacerbates atherosclerosis in type 2 diabetes mellitus - Fan, Bingge; Tang, Ting; Zheng, Xiao; Ding, Haixia; Guo, Peng; Ma, Hongqing; Chen, Yu; Yang, Yichao; Zhang, Lihui (Frontiers in Cardiovascular Medicine, 2023)
Background: Short sleep duration and poor sleep quality are important risk factors for atherosclerosis. The use of smart bracelets that measure sleep parameters, such as sleep stage, can help determine the effect of sleep quality on lower-extremity atherosclerosis in patients with type 2 diabetes. Objective: To investigate the correlation between sleep disorders and lower-extremity atherosclerosis in patients with type 2 diabetes. Methods: After admission, all patients were treated with lower-extremity arterial ultrasound and graded as havingwith diabetic lower-extremity vascular lesions according to the results. A smart bracelet was used to obtain the patients' sleep data. Then the correlation between sleep patterns and diabetic lower-extremity atherosclerosis, diabetic foot, and various metabolic indicexes was verified. Results: BetweenFrom August 2021 andto April 2022, we screened 100 patients with type 2 diabetes, of whomwith 80 completinged sleep monitoring. Univariate ordered logistic regression analysis indicated that patients with a sleep score of less thanbelow 76 (OR=2.707, 95%CI: 1.127--6.488), shallow sleep duration of more than or equal to 5.3 hours or more (OR=3.040, 95% CI: 1.005--9.202), more than or equal to 2.6 times of wakefulness at night of 2.6 times or more (OR=4.112, 95%CI: 1.513--11.174), and a deep sleep continuity score of less thanbelow 70 (OR=4.141, 95%CI: 2.460--615.674) had greater risk of high-grade lower limb atherosclerosis.The result of Mmultivariate ordinal logistic regression analysis revealed that the risk of having high-grade lower limb atherosclerosis was found higher for in patients with 2.6 or more instances of nighttimely wakefulness (OR= 3.975, 95%CI: 1.297--12.182) when compared with those with having nightly wakefulness less than 2.6fewer occurrences. The sleep time duration curve of patients with different grades of diabetic lower-extremity atherosclerosis was U-shaped. According to the results of the one-way analysis of variance, the higher the deep sleep continuity score, the lower the Wagner scale score for of diabetic foot (P<0.05).: Sleep disorders (long, shallow sleep duration, frequent wakefulness at night, and poor continuity of deep sleep) can worsen lower limb atherosclerosis in patients with type 2 diabetes.This finding can provide a new method for medical professionals to prevent and treat diabetic lower-extremity vascular lesions.